Ablation of Calsequestrin-1, Ca2+ unbalance, and susceptibility to heat stroke - Protasi, Feliciano; Girolami, Barbara; Serano, Matteo; Pietrangelo, Laura; Paolini, Cecilia (Frontiers in Physiology, 2022)
Introduction: Ca2+ levels in adult skeletal muscle fibers are mainly controlled by excitation-contraction (EC) coupling, a mechanism that translates action potentials in release of Ca2+ from the sarcoplasmic reticulum (SR) release channels, i.e. the ryanodine receptors type-1 (RyR1). Calsequestrin (Casq) is a protein that binds large amounts of Ca2+ in the lumen of the SR terminal cisternae, near sites of Ca2+ release. There is general agreement that Casq is not only important for the SR ability to store Ca2+, but also for modulating the opening probability of the RyR Ca2+ release channels. The initial studies: About 20 years ago we generated a mouse model lacking Casq1 (Casq1-null mice), the isoform predominantly expressed in adult fast twitch skeletal muscle. While the knockout was not lethal as expected, lack of Casq1 caused a striking remodeling of membranes of SR and of transverse tubules (TTs), and mitochondrial damage. Functionally, CASQ1-knockout resulted in reduced SR Ca2+ content, smaller Ca2+ transients, and severe SR depletion during repetitive stimulation. The myopathic phenotype of Casq1-null mice: After the initial studies, we discovered that Casq1-null mice were prone to sudden death when exposed to halogenated anaesthetics, heat and even strenuous exercise. These syndromes are similar to human malignant hyperthermia susceptibility (MHS) and environmental-exertional heat stroke (HS). We learned that mechanisms underlying these syndromes involved excessive SR Ca2+ leak and excessive production of oxidative species: indeed, mortality and mitochondrial damage were significantly prevented by administration of antioxidants and reduction of oxidative stress. Though, how Casq1-null mice could survive without the most important SR Ca2+ binding protein was a puzzling issue that was not solved. Unravelling the mystery: The mystery was finally solved in 2020, when we discovered that in Casq1-null mice the SR undergoes adaptations that result in constitutively active store-operated Ca2+ entry (SOCE). SOCE is a mechanism that allows skeletal fibers to use external Ca2+ when SR stores are depleted. The post-natal compensatory mechanism that allows Casq1-null mice to survive involves the assembly of new SR-TT junctions (named Ca2+ entry units) containing Stim1 and Orai1, the two proteins that mediate SOCE.